سیرت نگاری میں معجزات کا مطالعہ اور جدید رجحانات - ڈاکٹر سیّد ازکیا ہاشمی (FIKR-O NAZAR فکر ونظر, 2012)
The subject of miracles has always been given special attention in philosophical and scholastic discussions in every age by the Muslim as well as the non-Muslim scholars and intellectuals. The Sirah writers also presented many outstanding & comprehensive books on different aspects of miracles. The new scientific era has given new dimension to this discussion. Various viewpoints based on interpretation, comprehension and denial of miracles have broadened the study & research of this subject. These discussions open new areas of further research and investigation, which bring forth the truth & validity of the prophethood. New evidences and documents provided by geographical and archeological research has not only put a seal of authenticity on the genuineness & validity of these miracles, but also proved their possibility on rational & scientific grounds. The paper argues that these studies open doors to progress in science & technology for a Muslim scientist and strengthens his religious commitment. It alsosummaries these discussions, analyzes old & new sources of prophetic miracles and viewpoints & ideas of Muslim philosophers, Western orientalists, as well as contemporary Muslim Sirah writers, belonging to Indo Pak, Egypt & Arab countries.